(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In modern language education, the ability to speak fluently and effectively in real-life situations has become a primary goal. The Communicative Language Teaching (CLT) approach has emerged as a dominant paradigm for developing speaking skills in second and foreign language learners. Unlike traditional approaches that emphasize grammar and rote memorization, CLT prioritizes the functional use of language and encourages authentic communication